Death by chocolate ladyfingers - Graves, Sarah, 1951- (Graves, Sarah, 1951- Death by chocolate mystery., 2026)
The townsfolk of Eastport, Maine, know the best place to satisfy their sweet tooth is at Jacobia "Jake" Tiptree and Ellie White's bakery, the Chocolate Moose. But some people living in the island town have more sinister appetites As the sun sets on summer in Eastport, local celebrations are in full swing: and Jake and Ellie have their hands full supplying the most decadent of desserts for extended family gatherings, class reunions, and other catered events. The organizers for Eastport High School's Class of '86 reunion thought it would be fun for former schoolmates to dress up in costume for a masquerade ball. Unfortunately, masks cannot hide old grudges borne out of teenage angst. So when Cindy Munson's body is discovered murdered on the night of the dance, suspicion immediately falls upon Eastport High's one-time notorious school bully, Terry Lawson. Don attended the dance to apologize to those he harassed, only to be publicly rebuffed by Cindy. With the evidence stacked against him: Cindy's body was found in his car: and no memory of what happened, Don is arrested. He's more concerned about his six-year-old daughter going into child services than his own jail time. Remembering her own experiences in foster care, Jake volunteers to look after the little girl while conducting her own investigation into the night of the dance with Ellie. But someone doesn't want the amateur sleuths digging up past, humiliating secrets that may point to vengeful present-day motives: even if it means adding Jake and Ellie to a killer's body count ...